Use of C4d as a diagnostic tool to classify membranoproliferative glomerulonephritis - Nirupama Gupta; Dara N. Wakefield; William L. Clapp; Eduardo H. Garin (Nefrología, 2017)
Background: Membranoproliferative glomerulonephritis (MPGN type I, II and III) was reclassified in 2013 as MPGN and C3 glomerulopathy (C3G) based on the complement system activation mechanism. Objectives: To evaluate whether C4d, a component of the classical pathway, could be a diagnostic tool in differentiating between MPGN and C3G. Methods: We conducted a retrospective study of 15 MPGN type I, II and III and 13 minimal change disease (MCD) patients diagnosed between 2000 and 2012. C4d staining using the peroxidase method was employed. Results: Using the 2013 C3G consensus classification, the 15 MPGN types I, II and III biopsies were re-classified as MPGN (8) and C3G (7). Following C4d staining, of the 8 biopsies diagnosed as MPGN, 4 had classical pathway involvement [C1q (+), C3 (+), C4d (+)]; two had lectin pathway involvement [C1q (−), C3 (+), C4d (+)]; and, two were reclassified as C3G because the absence of C4d and C1q suggested the presence of the alternative pathway [C1q (−), C3 (+), C4d (−)]. Three of the seven C3G biopsies presented classical pathway involvement and were reclassified as MPGN. The alternative pathway was present in one of the other 4 biopsies considered to be C3G. Two C3G biopsies involved the lectin pathway and the one case of dense deposit disease had lectin pathway involvement. Conclusions: C4d staining may help to differentiate between MPGN and C3G. In addition, the lectin pathway could play a role in the pathogenesis of these glomerulopathies.